The COVID-19 Pandemic as a renewing factor of the Rural Development Model in Colombia - Mendoza Morales, Luisa Fernanda (2021)
This article presents a compilation of the history of rural development in Colombia, through the economic political complex, articulated with its reality and conflicts, which have generated an adverse episode for the competitiveness of the agricultural sector, and, in turn, it has caused an impact at the economic, social and cultural level. After analyzing the actors and the complexity of the agricultural sector regarding land ownership, it covers the impact of factors such as biological risks, economic openness and peace agreements as new alternatives to generate competitive, sustainable development for communities, environment, and territories. Finally, some alternatives are defined to achieve favorable changes in the sector, considering the implementation of the peace treaties, the decentralization of the country, the recovery of ancestral knowledge, and the strengthening of public institutions through research.